(3GdZQGeI ,GdMd ,Gdhba ,GdERGdI ,hSMH hEdZGA GdJQGNjUs - (3eMeO GdHGgj(B, (3CHhjhfSs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI(B,s, 2000)
(3GdLRA GdEOGQj GdYGe , GdQbGHI Ydi GdTQYjI , GdehVhYjI dLRGAGJ GdEOGQjI , GdQbGHI Ydi GdTQYjI GdELQGAGJ ddLRGAGJ GdEOGQjIs
Keywords: (3GdJQGNjUs; (3GdQbGHI GdbVGFjIs; (3GdZQGeIs; (3Gdhbas